Analisa Implementasi Rancangan Responsif Iklim pada Penginapan Firefly Eco-Lodge di Ubud, Bali - Madani, Made Agia Putri; Laskara, Gede Windu (Jurnal Arsitektur Lansekap; Vol.8, No.1, April 2022, 2022)
Climate responsive design implementation study at Firefly Eco-Lodge in Ubud, Bali . Indonesia is included in the tropical climate zone, namely tropical wet with a focus of 2 seasons, namely the rainy and dry seasons. Climate is a challenge that is part of the daily scope of activities. One of the studies included in it is the architectural aspect. Architecture itself is a design that associated with residential function where lodging as a place as a temporary residential as secondary function with the main focus of relaxation and recreation. Implementation of climate-responsive architecture need an effort to meet the needs and comfort of the community as users while also maintaining aesthetic and ecological principles. This study aims to understand the implementation of climate responsive architectural studies in lodging units and to determine the study of climate responsive architectural elements in lodging facilities. Found that building form, building layout, open plan room, landscaping, and material used are the key factor of climate responsive design that applied in Firefly Eco-Lodge. Circle & rounded shape created minimum solid surface exposed by solar radiation. Open plan concept creates natural wind flow that maintained comfort humidity. The method used is descriptive qualitative, which analyzes using climate-responsive architectural studies. Climate responsive principles implemented that meet with climate issues, such as solar radiation and thermal comfort, rainfall, air circulation, building shape, and the application materials and landscape that accommodate tropical climate issues.